Integrated Water Resources Management in Canada: the experience of watershed agencies. Issue 3 (4th May 2017) - Shrubsole, Dan; Walters, Dan; Veale, Barbara; Mitchell, Bruce
Abstract: Water agencies from 7 of the 10 Canadian provinces shared their experiences regarding history, successes, challenges and lessons learned with integrated watershed management. Based on these contributions, it is clear that an integrated approach does not mean 'all-encompassing'. Rather, it proposes desirable and feasible solutions through a systems approach based on sound technical information (e.g. biophysical and socio-economic), public engagement and monitoring. The roles of all participants must be clearly defined in order to promote success and facilitate implementation. Enduring and emerging challenges, such as adequate capacity and financing, engagement with Aboriginal communities and other stakeholders, and successful implementation, are identified.